PKB/AKT is involved in resumption of meiosis in mouse oocytes - Kalous, Jaroslav; Solc, Petr; Baran, Vladimir; Kubelka, Michal; Schultz, Richard M; Motlik, Jan (Biology of the cell, 2006)
BACKGROUND INFORMATION: In fully grown mouse oocytes, a decrease in cAMP concentration precedes and is linked to CDK1 (cyclin-dependent kinase 1) activation. The molecular mechanism for this coupling, however, is not defined. PKB (protein kinase B, also called AKT) is implicated in CDK1 activation in lower species. During resumption of meiosis in starfish oocytes, MYT1, a negative regulator of CDK1, is phosphorylated by PKB in an inhibitory manner. It can imply that PKB is also involved in CDK1 activation in mammalian oocytes. RESULTS: We monitored activation of PKB and CDK1 during maturation of mouse oocytes. PKB phosphorylation and activation preceded GVBD (germinal vesicle breakdown) in oocytes maturing either in vitro or in vivo. Activation was transient and PKB activity was markedly reduced when virtually all of the oocytes had undergone GVBD. PKB activation was independent of CDK1 activity, because although butyrolactone I prevented CDK1 activation and GVBD, PKB was nevertheless transiently phosphorylated and activated. LY-294002, an inhibitor of phosphoinositide 3-kinase-PKB signalling, suppressed activation of PKB and CDK1 as well as resumption of meiosis. OA (okadaic acid)-sensitive phosphatases are involved in PKB-activity regulation, because OA induced PKB hyperphosphorylation. During resumption of meiosis, PKB phosphorylated on Ser(473) is associated with nuclear membrane and centrosome, whereas PKB phosphorylated on Thr(308) is localized on centrosome only. CONCLUSIONS: The results of the present paper indicate that PKB is involved in CDK1 activation and resumption of meiosis in mouse oocytes. The presence of phosphorylated PKB on centrosome at the time of GVBD suggests its important role for an initial CDK1 activation.
Keywords: Protein Transport; myši; morfoliny; meióza; Meiosis; Threonine; 4-Butyrolactone; Serine; serin; transport proteinů; Female; CDC2 Protein Kinase; chromony; jaderný obal; Morpholines; kyselina okadaová; Nuclear Envelope; ženské pohlaví; aktivace enzymů; Centrosome; Enzyme Activation; threonin; fosforylace; techniky in vitro; Proto-Oncogene Proteins c-akt; oocyty; protoonkogenní proteiny c-akt; Oocytes; Animals; Okadaic Acid; Mice; zvířata; In Vitro Techniques; Phosphorylation; proteinkinasa CDC2; centrozom; Chromones; gama-butyrolakton